Superior mesenteric artery aneurysm: treatment with endovascular techniques: case report - Nogueira, Oriana; Duque, Mariana; Lopes, Catarina; Silva, Marta; Louro, João; Fernandes, Miguel; Tralhão, José G. (International Surgery Journal, 2022)
Superior mesenteric artery aneurysms (SMAA) are rare and associated with a high risk of rupture, morbidity and mortality. Their clinical presentation is heterogeneous, turning the clinical diagnosis into a difficult task-which can delay their treatment. We present a case of a patient with a SMAA, treated successfully with coil embolization.